Integrating Song-Based Multimedia into Arabic Listening Instruction: Development, Validation, and Effectiveness Testing - Lika Harnika; Mamluatu Solihah; Sutaman Sutaman (Universitas Islam Negeri Palangka Raya Raya, 2026)
Listening is a fundamental language skill that supports the development of overall communicative competence; however, Arabic listening instruction in secondary schools often remains constrained by conventional teaching approaches and limited use of engaging learning media. This study aimed to develop and evaluate the effectiveness of song-based video media for improving students’ Arabic listening skills. Employing a Research and Development (R&D) approach, the study adopted the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The developed media integrated Arabic songs, synchronized subtitles, visual animations, and scaffolded listening activities grounded in multimedia learning principles. The product was validated by media and content experts before being implemented with 24 eighth-grade students at MTs Al-Hidayah Batu, Indonesia. Data were collected through observations, interviews, validation questionnaires, student response surveys, and pretest–posttest assessments. Expert validation indicated that the media was pedagogically and technically feasible, achieving scores of 90% from the media expert and 80% from the content expert. The effectiveness results revealed a significant improvement in listening performance, with mean scores increasing from 53.54 to 81.45 and an average N-Gain score of 0.60, indicating moderate effectiveness. The findings suggest that song-based video media provides an engaging and effective approach to enhancing Arabic listening skills and contributes to the advancement of technology-enhanced Arabic language learning